(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines the correlation between students’ self-leadership in learning English and their English academic achievement among 8th-grade students in classes 8-3 and 8-5 at SMPN 1 Praya Timur. Based on the findings and data analysis, the research concludes that there is no significant correlation between the two variables. The results show that 11 students demonstrated high self-leadership, while 25 students exhibited very high self-leadership, with none falling into the low or moderate categories. This indicates that the majority of students possess high levels of self- leadership, as measured by the responses to the questionnaire. The data analysis supports the null hypothesis (Ho) and rejects the alternative hypothesis (Ha), with a Pearson correlation coefficient of -0.044, significantly lower than the r-table value of 0.199. This demonstrates a very low and statistically insignificant correlation between self-leadership and academic achievement in English. These findings suggest that fostering self-leadership alone may not be sufficient to enhance English academic performance for students at this level. A more comprehensive approach involving effective instructional strategies, supportive learning environments, and additional resources may yield better academic outcomes. Encouraging students to develop strong study habits, discipline, and consistent language practice may have a greater impact on improving their English academic performance than self-leadership skills alone.